GAYA KEPEMIMPINAN DEMOKRATIS DALAM PELAYANAN PUBLIK DI KELURAHAN BALLA PARRANG KECAMATAN RAPPOCINI KOTA MAKASSAR - Mustabir Daming; Rifdan (Universitas Negeri Makassar, 2023)
Leadership is very important in an organisation. leadership is a person's skills and ability to influence others to do something in accordance with the goals to be achieved. leading is a person's role to influence others in various ways. This study aims to describe the lurah's democratic leadership style in public services in Balla Parrang Village. The type of research used in this research is descriptive qualitative. Data collection techniques are done through observation, interviews, and documentation studies. The informants in the study were employees in the Balla Parrang village office, the head of the Community Association (RW) and the head of the RT. Determination of informants is done by using purposive sampling technique, in this study the analysis is done qualitatively. The results showed that the head of Balla Parrang village as a leader with a democratic and charismatic leadership style. In addition, in the leadership style of Balla Parrang village head gives a positive influence to the staff because Balla Parrang village head for always conveying the importance of discipline.